Production of sodium lauryl sulfate from coconut fatty alcohol - Caparos, Michael; del Rosario, Faye.; Fernandez, Fredeiz; Lim, Edward Cedric (Diliman, Quezon City College of Engineering, 1998)
Product: Sodium lauryl sulfate -- Total capital: Php 181,360,958.00 -- Fixed capital: Php 49,692,560.87 -- Working capital: Php 131,668,397.00 -- Product cost: Php 33.18/kg -- Break-even production rate: 4,205.152 MTY -- Plant capacity: 25,000 MTY -- Break-even price: Php 35.17/kg -- Current selling price: Php 45.00/kg -- Suggested selling price: Php 45.00/kg -- ROI: 40.41% -- Pay-out period: 0.53 years (w/o interest), 9.13 years (w/ interest)
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Chemical plants